Decision Making Performance of Business Data Analytical Capabilities: The Mediating Effect of Analytics Competency - Fattah , Ikhsan A; Kartono , Rano; Hamsal , Mohammad; Furinto , Asnan (International Journal of Membrane Science and Technology, 2023)
This research study investigates the mediating influence of analytics competency (AC) on the relationship between business data analytical capabilities (BDAC) and decision-making performance (DMP). Using a quantitative approach, 167 managers with experience and competence in using data in Indonesian public service sector organizations were empirically evaluated. Structural Equation Modeling analysis was applied to examine the impact of BDAC on DMP and mediating effects of AC on this relationship. The results demonstrate that BDAC and AC significantly influence DMP, and BDAC significantly affects AC. Notably, AC was identified as a complementary mediator in the relationship between BDAC and DMP, explaining the majority of their effects. These findings suggest the significance for organizational leaders and managers to develop plans that nurture BDAC and the use of AC to maximize the business's utilization of big data. Thus, organizational leaders and managers can determine the policies and strategies needed to extract value from data, determine the direction of the organization in data-driven decision-making, thereby building better and faster decision quality through AC and BDAC. Moreover, the study highlights opportunities for future studies, including comparative analysis across different organizations, experimental research on AC and DMP, and the application of concurrent or sequential mixed methods to explore context and process relationships among variables.